National standards of pharmaceutical education in the context of reforming legislation of higher education - І. M. Alieksieieva (Zaporozhye State Medical University, 2018)
Socially significant steps of Ukraine in the issue of European integration are measures to reform the legislation on higher education in the context of the Bologna process, namely: the adoption of the National Qualifications Framework and the new edition of the Law of Ukraine "On Higher Education." The National Qualifications Framework (NQF, 2011) provides for "the introduction of European standards and principles to ensure the quality of education, taking into account the requirements of the labor market to the competence of specialists." According to formal characteristics, NQF is a matrix with static support elements - descriptors, which determine the vector of movement to a specific goal. The legal basis for the modernization of educational activities and standards of higher education was the new edition of the Law of Ukraine "On Higher Education" (2014). The purpose of the article is a scientific and analytical study of the process of forming national standards for higher education, in particular, the standards of pharmaceutical higher education. Materials and methods. The study was based on the analysis of normative and legal and other normative acts on higher education, the issues of standardization of higher education and the systematization of qualifications, as well as scientific developments on this issue. Methods of research - bibliographic, linguistic, contextual, substantive-legal, comparative-legal, generalization, description of results. Results. Updating the wording of the Law of Ukraine "On Higher Education," which is the basic normative legal act of higher legal action in higher education, the adjustment of its basic principles, concepts and approaches, objectively entailed the renewal of the entire regulatory and legal framework regulating the organization of higher education. Equally, this also affected the standards of higher education. This issue in the Act is reserved Section III: Standards of educational activity and higher education, where the terminological concept and the general algorithm for the formation of the standard of higher education is precisely fixed. The draft standard of higher education in specialty 226 "Pharmacy" (master's degree) is developed as a result of intellectual cooperation of the team of high-ranking scientists and teachers of the pharmaceutical higher school. It forms the basis for modernization of higher professional education on the way of integration into the European educational space. Conclusions: The draft standard of higher education developed by the academic community on specialty 226 "Pharmacy" (master's degree) is based on the relevant provisions of the Law of Ukraine "On Higher Education" and the Methodological Recommendations for its development and creates a basis for the modernization of higher professional education on the path of integration into the European educational space . The question on urgent proper actions of the National Agency for Quality Assurance of Higher Education and MES of Ukraine, for its implementation as a legitimate standard of higher education in the relevant specialty. The existing draft standard of higher education in specialty 226 "Pharmacy" has the potential for improvement.